Electrochemical Sensor of Levofloxacin on Boron-Doped Diamond Electrode Decorated by Nickel Nanoparticles - Prastika Krisma Jiwanti; Irfansyah Rais Sitorus; Grandprix Thomryes Marth Kadja; Siti Wafiroh; Yasuaki Einaga (Indonesian Journal of Chemistry, 2022)
Levofloxacin (LEV) was known as one of the fluoroquinolone antibiotics that widely used as an antibacterial agent. Monitoring of LEV is important due to its negative side effect on humans. The determination of LEV was studied for the first time on nickel modified on a boron-doped diamond (NiBDD) electrode using the square wave voltammetry (SWV) method to improve the catalytic and sensitivity of the sensor. The response was linear in the range of 30–100 mM LEV. LEV sensor on NiBDD was found to be selective in the presence of urea, glucose, and ascorbic acid interferences. Good reproducibility with % a relative standard deviation of 1.45% (n = 10) was achieved. Therefore, the NiBDD electrode could be potentially applied for the real detection method of LEV.